2017
DOI: 10.1002/hep.29257
|View full text |Cite
|
Sign up to set email alerts
|

The novel intracellular protein CREG inhibits hepatic steatosis, obesity, and insulin resistance

Abstract: The results of our study provides evidence that CREG is a robust suppressor of hepatic steatosis and metabolic disorders through its direct interaction with ASK1 and the resultant inactivation of ASK1-JNK1 signaling. This study offers insights into NAFLD pathogenesis and its complicated pathologies, such as obesity and insulin resistance, and paves the way for disease treatment through targeting CREG. (Hepatology 2017;66:834-854).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 42 publications
1
35
0
Order By: Relevance
“…Hepatocyte‐specific Creg knockout ( Creg ΔHep ) mice and hepatocyte‐specific Creg transgene ( Creg ‐HTG) mice in the C57BL/6J background were generated as previously described . We used albumin‐Cre recombinase transgenic (TG) mice (albumin‐Cre TG mice) and Creg flox/flox mice to intercross and generate mice with the Creg gene specifically deleted in hepatocytes (albumin‐Cre/+ Creg flox/flox mice, abbreviated as Creg ΔHep ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hepatocyte‐specific Creg knockout ( Creg ΔHep ) mice and hepatocyte‐specific Creg transgene ( Creg ‐HTG) mice in the C57BL/6J background were generated as previously described . We used albumin‐Cre recombinase transgenic (TG) mice (albumin‐Cre TG mice) and Creg flox/flox mice to intercross and generate mice with the Creg gene specifically deleted in hepatocytes (albumin‐Cre/+ Creg flox/flox mice, abbreviated as Creg ΔHep ).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, Creg also exhibits protective properties against heart injury induced by I/R insult through autophagy and anti‐apoptosis . A recent study also suggested that Creg is a suppressor of hepatic steatosis and metabolic disorders through its interaction with MAPK/apoptosis signal‐regulating kinase 1 (ASK1)–c‐Jun N‐terminal kinase 1 (JNK1) signaling . Considering the regulatory effects of Creg on cardiovascular cellular events, in particular of inflammation and cell death, which also directly correlate with the progression of hepatic I/R injury, and the characteristics of Creg in regulating MAPK signaling, we hypothesized that Creg prominently participates in the progression of hepatic I/R‐induced liver injury.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…ASK1 is normally held in an inactivated state bound to various inhibitors such as thioredoxin or glutathione (GSH) S ‐transferases, which are redox sensitive so that ROS can release ASK1 from inhibition . In addition, CASP8‐ and FADD‐like apoptosis regulator (cFLIP) and cellular repressor of E1A‐stimulated genes (CREG) have been shown to interfere with the dimerization of ASK1, preventing activation . Therefore, conditions in which the expression of cFLIP or CREG is inhibited can lead to enhanced ASK1 activation.…”
Section: The Jnk Signaling Pathway In the Liver: Recent Advancesmentioning
confidence: 99%
“…Many ASK1 regulatory mechanisms have been described previously and could represent potential therapeutic targets for NASH. For instance, TRAF1, DKK3, and CREG modulate hepatic ASK1 phosphorylation and the severity of NASH; CFLAR targeting of ASK1 interrupts its dimerization and activation in NASH; and TNFAIP3 mediates the deubiquitination and inactivation of hepatic ASK1during NASH . Given that Lys63‐, Lys29‐, and Lys11‐linked ubiquitination is critical in activation of ASK1 during NASH progression, identification of a molecule that regulates one or some of these types of ubiquitination in ASK1 could provide an alternative or an adjuvant therapeutic target for NASH.…”
Section: Discussionmentioning
confidence: 99%